Development of Device for Pressure Control System in a Freezer of Pressed-Plate Type - Surya Abdul Muttalib; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Arifin Dwi Saputro (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The process of freezing foodstuffs can be done by using a cold metal plate that is in contact with the frozen material (contact plate freezing). The magnitude of contact Force Compressive applied needs to be controlled so as not to damage the frozen material. The purpose of this study was to develop and evaluate the performance of a Force Compression control system on a contact plate freezer. The Force Compression control system was composed of a load cell mounted on a Force Compression device, connected to a set of controllers consisting of an HX711 module, ATM Mega Arduino and a computer using the Borland Delphi 7 language. The results showed that the developed system was able to control the compression process of the equipment by turning off voltage input of the motor when the specified setting point has been reached. The results of Force Compression values when the motor in off position for the setting points of 50, 100, 150, 200, 250, and 300 kg.m/s2 were 58.25, 110.25, 162.67, 213.83, 264.55, and 317.61 kg.m/s2, respectively. There was a difference that gradually increased with increasing setting point value, where the real Force Compression values when the motor off were higher than the setting point values. The relationship between real Force Compression and setting point Force Compression could be given in the form of a linear regression equation y = 1.06897x + 6.14667 with a value of R2 = 0.99, RMSE 1,53 and MAPE 11,75 %. Keywords:   Arduino, Control system, Force Compression, Force Compression plate, Setting point